2014
DOI: 10.1039/c3an01443f
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of silver nanoparticles and dissolved species of silver in culture medium and cells by AsFlFFF-UV-Vis-ICPMS: application to nanotoxicity tests

Abstract: A methodology based on Asymmetric Flow Field-Flow Fractionation (AsFlFFF) coupled with UV-Vis absorption spectrometry and ICP mass spectrometry (ICPMS) has been developed and applied to the study of silver nanoparticles (AgNPs) and dissolved species of silver in culture media and cells used in cytotoxicity tests. The effect of a nano-silver based product (protein stabilized silver nanoparticles ca. 15 nm average diameter) on human hepatoma (HepG2) cell viability has been studied. UV-Vis absorption spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 32 publications
(42 reference statements)
3
52
0
Order By: Relevance
“…Within this study, the abundance of ionic Ag in the original nanoparticle suspensions or in mixed culture media was not further studied. It is known that especially for bio-available Ag ENPs and if these ENPs are additionally of smaller sizes (b 20 nm), this might be of influence [13]. Obtained fractograms showed one resp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this study, the abundance of ionic Ag in the original nanoparticle suspensions or in mixed culture media was not further studied. It is known that especially for bio-available Ag ENPs and if these ENPs are additionally of smaller sizes (b 20 nm), this might be of influence [13]. Obtained fractograms showed one resp.…”
Section: Resultsmentioning
confidence: 99%
“…A large range of human cell lines is available for in vitro testing. Human liver cells like HepG2 and colon Caco2 cells are well studied Microchemical Journal 120 (2015) 45-50 cell lines in relation to nanosilver [12,13]. As ENPs tend to end up in phagocytizing cells, a human acute monocytic leukemia cell line (THP-1) can be used for exposure testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AF4 fractogram revealed that the size of AgNPs increased from 17 nm to 32 nm after AgNPs were incubated in the culture medium for 24 h. UV-vis spectra showed no differences at the absorbance maximum wavelength before and after the incubation, indicating no obvious aggregation occurred. The increment in the size distribution probably due to the"protein corona" effect [25]. Compare with other techniques like TEM, AF4 can get similar results but is much faster and simpler [21,23].…”
Section: +mentioning
confidence: 83%
“…However, KOH and NaOH may induce the aggregation of AgNPs [28], and TMAH, which does not change the integrity of AgNPs in short times, appears more suitable for digesting complex samples. AgNPs associated with the cultured HepG2 cells were readily identified by AF4-ICP-MS after a digestion process based on TMAH and Triton X-100 [25]. FFF can also find their way in analyzing AgNPs in consumer products [20], dietary supplements [20], and untreated wastewater [29], showing promises to study the environmental fate of AgNPs in the complex systems.…”
Section: +mentioning
confidence: 99%